Effects of dance therapy on the rehabilitation of patients with cancer: a systematic review (Research, Society and Development, 2023)
Introduction: The diagnosis of cancer causes several changes in the lives of human beings, generating impacts on the emotional, physical and psychological state. Fear, stress and sadness usually interfere in quality of life, so dance therapy is a therapeutic method that will serve as an instrument for health rehabilitation, using dance as a means to achieve functional balance and self-esteem of people diagnosed with cancer. Objective: To describe the effectiveness and benefits of dance therapy, in order to emphasize complementary therapies that are important methods during treatment. Material and Methods: Systematic review, in which articles were selected between 2018 and 2021. Published in both Portuguese and English languages in the electronic database as Latin American Caribbean Literature in Sciences of Health (Lilacs), Pubmed, Scientific Electronic Library Online (Scielo) and Physiotherapy Evidence Database (PEDro). Results: The search for data was summarized in a flowchart, in which 546 articles were found based on the combination of descriptors in health science, but after reading, 8 scientific articles were selected divided into three categorical themes; psychological and social. Conclusion: Dance therapy provides physical, psychosocial benefits directly in functional capacity and quality of life during choreography and musical rhythms, influencing functional capacity, self-image, acceptance and especially quality of life.